Growth rate and meat quality of guinea fowl kept in farm conditions - Vladimir A. Zabiyakin; Sergey A. Zamyatin (Аграрная наука Евро-Северо-Востока)
The research (2018-2019) was conducted in the conditions of a peasant farm in the Voronezh region. The paper evaluates the indicators of the growth rate and meat productivity of the preserved gene pool groups of guinea fowl. The experiment involved three groups of daily guinea fowl of 200 heads of different genetic origin: lines of the Volga white breed (the original VB-4, selected by the rate of live weight gain and reproductive characteristics; autosex VBA-1, selected by the color of down, feather and productive characteristics) and gray-speckled guinea fowl of unknown origin. Studies have shown that the live weight of guinea fowl of the VBA-1 line exceeded the live weight of poultry from other groups of guinea fowl, a significant excess was noted at 8, 12 and 13 weeks of age. The greatest coefficient of variation of the trait was observed at 8 weeks of age. The analysis of relative gain in live weight of guinea fowl showed that up to 10 weeks of age, the highest relative growth rate of guinea fowl of all experimental groups was observed (14.0-17.0 %). Starting from the age of 11 weeks, this indicator gradually decreased (4.3-13.4 %). It was found out that under the same conditions of keeping and feeding, the feed costs per 1 kg of live weight gain in guinea fowls of the VBA-1 line were less by 0.09-0.16 kg (3.11-6.33 %) compared to poultry of the VB-4 line and by 0.2-0.4 kg (5.49-12.82 %) compared to their gray-speckled peers. The results of anatomical cutting of guinea fowl carcasses showed that the experimental groups of poultry significantly (P< 0.05) differed among themselves in the degree of development of internal organs and tissues. The yield of edible parts was 60.2-61.1 %, depending on the group of poultry. The large live weight noted by us in linear poultry is the reason for their better meat productivity, which is directly related to an increase in the absolute mass of the eviscerated carcass, its edible parts, muscles and bones. Based on the data obtained, the optimal age of poultry slaughter for meat was determined at 10-12 weeks of life.